2013
DOI: 10.2188/jea.je20120180
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Tooth Loss Among Community-Dwelling Middle-aged and Elderly Japanese Men

Abstract: BackgroundUsing data from a large-scale community-based Japanese population, we attempted to identify factors associated with tooth loss in middle-aged and elderly men.MethodsA total of 8352 men aged 40 to 79 years who lived in the north of the main island of Japan and underwent health checkups were enrolled between 2002 and 2005. Number of teeth was assessed by the question, “How many teeth do you have (0, 1–9, 10–19, or ≥20)?”. On the basis of the answer to this question, participants were classified into 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 34 publications
10
44
0
3
Order By: Relevance
“…Ando et al found that smoking, low education level, and poor nutritional status, had an association with tooth loss among middle-aged and elderly Japanese population [27], this agrees with our findings in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Ando et al found that smoking, low education level, and poor nutritional status, had an association with tooth loss among middle-aged and elderly Japanese population [27], this agrees with our findings in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…This is particularly evident in socioeconomic factors. Previous studies revealed that a low education level was associated with tooth loss [6,23]. The reason is that education level is associated with the utilization of dental care and oral health behavior [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors affecting tooth loss have been suggested, including sociodemographic factors (e.g., age and educational attainment) [5,6], lifestyle and health factors (e.g., nutritional status, smoking habits, and current history of disease) [5,6,7,8,9], and oral health conditions and behaviors (e.g., complaint of oral condition and dental care visits) [10,11]. Distance to dental care facilities is also a potential factor for tooth loss, especially in rural areas [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an examination of 8352 men aged 40–79 years showed that the male ex‐smokers (aged 65–79 years) had a significantly higher risk of having 19 or fewer teeth as compared with their non‐smoking counterparts. The amount of destruction was directly proportional to the duration of smoking among older adults …”
Section: Etiopathogenesis Of Chronic Periodontitis In Elderly Smokersmentioning
confidence: 99%